Intersectionalities and Care Work: Bolivian Circular Migration in Northern Chile - Garcés-Estrada, Carolina (2021)
This article analyzes the multiple oppressions in the care work and in the circular migration of Bolivian women in the north of Chile. The analysis focuses on the intersectional approach, as it further stresses and deepens the field of analysis of circular migration in cross-border areas, where social inequalities, substantially social class and race, tend to be legitimized and consolidated. Here findings emerge for the specific case, related to migratory status, racialization and sexualization in the international division of labor. To think about these processes, intersectionality operates as a critical framework for the global structures and power relations that produce and reproduce the relations of inequality that affect Bolivian migrant women.